1973
DOI: 10.1073/pnas.70.7.2072
|View full text |Cite
|
Sign up to set email alerts
|

Action of Rifamycin Derivatives on RNA Polymerase of Human Leukemic Lymphocytes

Abstract: The mechanism of inhibition of human RNA polymerase by four rifamycin derivatives was investigated. Derivative AF/013 (3-formyl rifamycin SV: 0-noctyloxime) with strong hydrophobic side chains prevents the polymerase from binding to DNA and also affects the size of RNA synthesized. Derivative benzyl-2'-methylpyrrolo[3,2-cJ-4-desoxy-rifamycin SV) only affects RNA synthesis when RNA polymerase has been previously incubated with the drug or when the reaction was performed at high salt concentration [0.14 M (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
5
0

Year Published

1975
1975
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 13 publications
2
5
0
Order By: Relevance
“…We reported that the inhibition appeared to be the result of a strong cooperative interaction among drug molecules which bind to a hydrophobic region of the reverse transcriptase (Gurgo et al, 1974). As previously found in the inhibition of bacterial (Riva and Silvestri, 1972, for a review), T7 bacteriophage-induced (Chamberlin and Ring, 1972), and mammalian RNA polymerases (Meilhac et al, 1972, andTsai andSaunders, 1973) by rifamycin derivatives, these compounds are more effective when they interact with the reverse transcriptase before initiation of polymerization (Wu and Gallo, 1974). In this article, we present evidence that the differences in the structure of the side chain confer on several rifamycin derivatives the ability to inhibit the viral DNA polymerase with different modes of action.…”
supporting
confidence: 54%
“…We reported that the inhibition appeared to be the result of a strong cooperative interaction among drug molecules which bind to a hydrophobic region of the reverse transcriptase (Gurgo et al, 1974). As previously found in the inhibition of bacterial (Riva and Silvestri, 1972, for a review), T7 bacteriophage-induced (Chamberlin and Ring, 1972), and mammalian RNA polymerases (Meilhac et al, 1972, andTsai andSaunders, 1973) by rifamycin derivatives, these compounds are more effective when they interact with the reverse transcriptase before initiation of polymerization (Wu and Gallo, 1974). In this article, we present evidence that the differences in the structure of the side chain confer on several rifamycin derivatives the ability to inhibit the viral DNA polymerase with different modes of action.…”
supporting
confidence: 54%
“…Early studies with rifamycin suggest that these molecules bind tightly to the polymerase, with dissociation half-lives approaching 2 hrs, [52] and prevent the polymerase from binding to DNA [53]. Rifaximin safety profile is attributed to its poor absorption due to a pyridoimidazole ring [54].…”
Section: Nmes Targeting Non-human Enzymesmentioning
confidence: 99%
“…The complexity of the RNA polymerase reaction makes studies on post-initiation events relatively difficult. Several factors, such as reinitiation of the enzyme on the template, altered initiation sites on different templates, effects of divalent ions and salt concentrations (Meilhac and Chambón, 1973;Lili and Hartmann, 1973;Tsai and Saunders, 1973 tein (bovine serum albumin, BSA) on the inhibition of RNA polymerase II was also investigated. BSA reduced the extent of inhibition by AF/013, but did not alter the competitive nature of inhibition.…”
mentioning
confidence: 99%